Penerapan metode TOPSIS dalam menentukan Reseller Terbaik Rumah Madu Syahara. - Anggi Hadi Wijaya (GLOBAL SCIENTS PUBLISHER, 2025)
In the competitive honey industry, selecting the best reseller is a key factor in enhancing distribution effectiveness and business growth. Rumah Madu Syahara faces challenges in objectively evaluating reseller performance. Therefore, this study applies the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method to determine the best reseller based on six main criteria: total sales, order frequency, reseller loyalty, payment timeliness, product returns, and promotional activity. Data from ten active resellers were analyzed through the TOPSIS method, including normalization, weighting, and determining positive and negative ideal solutions. The results indicate that the reseller coded A6, named Wahyu Fitri, achieved the highest preference score of 0.8462, making them the best reseller. This study proves that the TOPSIS method is effective in objectively and data-driven reseller evaluation. The findings can serve as a reference for businesses to improve reseller performance and optimize marketing strategies.